Isomerismo cis-trans: de Werner aos nossos dias - Queiroz, Salete Linhares [UNESP]; Batista, Alzir Azevedo (Sociedade Brasileira de Química, 1998)
In coordination chemistry the study of geometrical isomerization and reactivity of specific isomers is a topic of major importance. The preparation of specific isomers often requires considerable complexity, and it is important to acquire a sense of what is involved in studying isomerism in laboratory. If it is difficult sometimes to prepare pure isomers, it is not easier to understand the mechanisms of isomerization reactions since studies on this subject have shown conflicting results and diferent interpretations on the same system have been reported in the literature. Although cis-trans isomerism in octahedral metal complexes is a common occurrence, there are relatively few studies reporting how these isomerizations occur. This paper gives an overview on cis-trans isomerization processes and identification of these species.
Cis-trans isomerism: from Werner to the present days
Keywords: complexes; isomerism; cis-trans